ANALISIS RASIO KEUANGAN SEBAGAI TOLAK UKUR KINERJA KEUANGAN KUD KARYA SAWIT DESA BUKIT KRATAI KEC. RUMBIO JAYA KAMPAR - Fresty Harnum; Gimin '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: Cooperatives include liquidity, solvency, activity, and profitability or so-called financial ratio analysis. Benefits of using financial ratios are useful for all management capable of related parties in the company this is because the analysis of financial ratios used to measure the performance of the company from time to time or compare with similar companies, and as a decision-making tool for users of financial statements. In this study aims to determine the financial performance KUD Karya Sawit 2010 to 2014 based on the analysis of liquidity ratios, solvency ratios and profitability ratios. The data obtained comes from the accountability report or financial report which includes the balance sheet, income statement and net wealth report KUD Karya Sawit 2010 to 2014. Data analysis technique in this research is descriptive quantitative analysis method. By using this method the results of research in the form of financial statement data will explain how the financial performance of the cooperative. The financial statements are then analyzed using liquidity ratios, solvency ratios, and profitability ratios. From the research results obtained can be concluded that the financial performance based on liquidity ratios, solvency ratios, and profitability ratios have poor performance. Based on this research, it is recommended that KUD Karya Sawit cooperative should be able to increase profit margin to be able to suppress ineffective operational costs, and maximize the utilization of resources in the form of investment and capital to increase cooperative profit.Keywords: Financial Ratio, Financial Performance, and Cooperative